The sense of my screaming skin. An investigation into the colouring process of Amalric Walter (1870-1959) using metallic salts in pâtes-de-verre - Stewart, Max (The University of Edinburgh, 2010)
The research undertaken in this PhD builds on a previous study into the lost methodology and techniques of the French pâtes -de -verre artist Amalric Walter (1870 -1959). This PhD clarifies those working methods, develops his guiding principles, and moves forward the techniques into the 21st century.

My research takes three simultaneous paths of investigation: Historic, Scientific and Personal. As well as being individual studies in themselves they inform and illuminate each other.

In the attempt to clarify the original subject matter, more questions are raised about the development of the late French Art Nouveau pâtes -de -verre movement, and why Walter's techniques differed so greatly from those employed by his fellow artists. The research also investigates the historical accuracy of the creative world from which pâtes -de -verre sprang, and offers an alternative view of a process that has continued unbroken across two millennia. The results and their conclusions are laid out in the form of three separate books that culminate in a body of my own personal art work. Ultimately the study increases our knowledge of what pâtes -de -verre is, how it can be made, and confronts accepted artistic boundaries of what pâtes -de -verre can illustrate.